Factors Affecting the Performance of Community Nurses on Palliative Care in Bangkok Metropolitan - Suksawat, Kannarisa; Kalampakorn, Surintorn; Amnatsatsue, Kwanjai (Journal of The Royal Thai Army Nurses, 2023)
This cross-sectional study was conducted to examine the relationship between the factors affecting the performance of community nurses on palliative care in Bangkok. Participants were 172 nurses, working at the public health centers in Bangkok Metropolitan selected through the stratified random sampling. Data was collected using the self- administered questionnaires and analyzed by using the descriptive statistics, Pearson’s product-moment correlation coefficient and Stepwise multiple regression analysis. The result revealed that the community health nurses at the public health centers had a high level of overall performance on palliative care ( = 3.22, SD = 0.46). The factors that could significantly predict the performance of community nurses on palliative care in Bangkok were organization policy, co-worker relationship, social environment, and method of work. These predictors altogether could explain 70.1% of variance in performance on palliative care. It is suggested that public health administrators should have a policy and provide appropriate tools and equipment to support palliative care services. Multidisciplinary involvement should also be promoted to further improve the quality of nursing practices in palliative care.